2016
DOI: 10.1016/j.cmi.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Empirical and targeted therapy of candidemia with fluconazole versus echinocandins: a propensity score–derived analysis of a population-based, multicentre prospective cohort

Abstract: We compared the clinical efficacy of fluconazole and echinocandins in the treatment of candidemia in real practice. The CANDIPOP study is a prospective, population-based cohort study on candidemia carried out between May 2010 and April 2011 in 29 Spanish hospitals. Using strict inclusion criteria, we separately compared the impact of empirical and targeted therapy with fluconazole or echinocandins on 30-day mortality. Cox regression, including a propensity score (PS) for receiving echinocandins, stratified ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In agreement with our findings, Lopez-Cortes et al studied a real-world prospective cohort of patients with candidaemia treated with empirical or targeted fluconazole and also did not observe an increase in 30-day mortality compared with patients treated with echinocandins. Furthermore, the use of fluconazole was not related to a higher incidence of clinical failure or persistent candidaemia, which, in fact, could more likely be associated with biofilm maintenance [28,29].…”
Section: Discussionmentioning
confidence: 89%
“…In agreement with our findings, Lopez-Cortes et al studied a real-world prospective cohort of patients with candidaemia treated with empirical or targeted fluconazole and also did not observe an increase in 30-day mortality compared with patients treated with echinocandins. Furthermore, the use of fluconazole was not related to a higher incidence of clinical failure or persistent candidaemia, which, in fact, could more likely be associated with biofilm maintenance [28,29].…”
Section: Discussionmentioning
confidence: 89%
“…Despite some studies showing the superiority of echinocandins over fluconazole, a propensity score-derived analysis of a population-based, multicenter prospective cohort has demonstrated that, in patients with candidemia, therapy with fluconazole did not show a significant association with mortality either in the empirical or targeted therapy [52]. These results were similar among patients with severe sepsis and septic shock.…”
Section: What Are the Common Beliefs That Have Been Contradicted By Rmentioning
confidence: 83%
“…173 Targeted therapy is based on microbiological evidence of an IC (e.g., a positive blood culture for Candida species or positive cultures of a normally sterile site). 174 Moreover, once candidemia is diagnosed, an adequate source control of the infection (catheter removal, drainage, debridement) should be also performed as soon as possible. 3,27 Antifungal Agents…”
Section: Treatmentmentioning
confidence: 99%
“…185 However, in a prospective study conducted in 29 hospitals in Spain with less severe patients (only 30% being in the ICU), empirical treatment with fluconazole was not associated with increased 30-day mortality compared with echinocandins in patients with candidemia. 174 There has been concern about the use of echinocandins as primary therapy against C. parapsilosis because of higher in vitro minimum inhibitory concentrations (MICs). A retrospective study on 307 episodes of C. parapsilosis candidemia demonstrated no difference in 30-day mortality between patients receiving an echinocandin as compared with fluconazole.…”
Section: Treatmentmentioning
confidence: 99%